Pelatihan Edupreneur Pembuatan VCO Berbasis Fermentasi untuk Guru dan Siswa di SMPIT Az-Zahira Khatulistiwa Kubu Raya - Ahmad Faisal Amri; Hanum Mukti Rahayu; Mahwar Qurbaniah; Arif Didik Kurniawan; Nuri Dewi Muldayanti; Diana (BALE LITERASI, 2026)
This community service program conducted at SMPIT Az-Zahira Khatulistiwa, Kubu Raya, aims to enhance the entrepreneurial literacy, creativity, and independence of both students and teachers. This objective was achieved through training in fermentation-based Virgin Coconut Oil (VCO) production, positioning it as an economically valuable product derived from local potential, while concurrently implementing the Pancasila Student Profile Strengthening Project (P5). The implementation methodology encompassed several stages: socialization, the delivery of conceptual materials on entrepreneurship and food safety, hands-on practice in VCO production, and packaging mentoring. The active participation of the attendees yielded positive outcomes, evidenced by a significant increase in their conceptual understanding from 42% to 85%. Furthermore, beyond acquiring technical proficiency in VCO production, the participants demonstrated enhanced entrepreneurial characteristics, including creativity, collaboration, and responsibility. In conclusion, this training has proven highly effective as a contextual learning medium, successfully honing 21st-century skills while simultaneously integrating the noble values of Pancasila.